PELAKSANAAN FUNGSI BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPETAN TIMOR TENGAH UTARA DITINJAU DARI PERATURAN DAERAH KABUPATEN TIMOR TENGAH UTARA NOMOR 9 TAHUN 2008 TENTANG ORGANISASI DAN TATA KERJA BADAN PERENCANAAN PEMBANGUNAN DAERAH, INSPEKTORAT DAN LEM - Feka, Gregorius Triyanto; Tupen, Rafael Rape; Udju, Hernimus Ratu (Petitum Law Journal, 2024)
This study discusses two issues, namely: (1) To what extent is the implementation of the function of the Regional Development Planning Agency of North Central Timor Regency in terms of the Regional Regulation of North Central Timor Regency Number 9 of 2008 concerning the Organization and Work Procedures of the Regional Development Planning Agency, Inspectorate and Other Regional Technical Institutions of North Central Timor Regency? (2) What are the factors that are obstacles in the implementation of the functions of the Regional Development Planning Agency of North Central Timor District? The research method used is the empirical method, which is research conducted directly to related parties to obtain primary data directly from respondents. The data collection techniques used are: observation, interviews, and documentation. The results of research and discussion: (1) The implementation of the functions of the Regional Development Planning Agency (BAPPEDA) in terms of Regional Regulation Number 09 of 2008 concerning the Organization and Work Procedures of the Regional Development Planning Agency, Inspectorate and Other Regional Technical Institutions of North Central Timor Regency in the process of regional development planning in North Central Tmor Regency is through Village/Village level Development Planning Deliberations, District Development Planning Deliberation, and finally the District Government Work Plan Development Planning Deliberation where the aspirations and proposals of the community are as a determination of the formation of the Regional Long-Term Development Plan (RPJPD), Regional Medium Term Development Plan (RPJMD) and then make a Regional Apparatus Work Plan (RKPD), as a strategy used by BAPPEDA for development programs in North Central Timor District. (2) Inhibiting factors in the implementation of the function of providing support for the implementation of local government in the field of development planning and the function of guidance and implementation of tasks in accordance with the scope of Bappeda's duties in North Central Timor Regency. There are several obstacle factors such as: Aspects of Geography and Domography related to human resources, aspects of community welfare, aspects of public services, and aspects of regional competitiveness.